Pengembangan model pembelajaran Student Center Learning (SCL) berbasis aktivitas pada mata kuliah Pendidikan Pancasila di Fakultas Hukum - Nurmalita Ayuningtyas Harahap; Karimatul Ummah; Ayunita Nur Rohanawati; Siti Ruhama Mardhatillah (Refleksi Pembelajaran Inovatif, 2020)
This research is a development research of learning methods for Pancasila Education in the Faculty of Law UII using Student Center Learning (SCL) learning methods based on student activities. Learning problems that will be solved in this study include: First, is how the SCL learning method based on activity in the Pancasila Education Course at the Faculty of Law UII. Second, is whether the SCL method based on activity in the Pancasila Education subject is in accordance with Learning Outcomes. This study uses experimental research methods and class action (experiment and action research) by using 2 parallel classes, one class as an experimental class implementing SCL learning methods based on activity, while the other class is used as a class that does not use SCL methods based on activity. The results showed: First, the right methods to be used in learning Pancasila Education courses include brain stroming, discussion, observation, and presentation of the results of discussion and observation, and reflection. Second, classes that use the activity-based SCL learning method are more effective and efficient at achieving the learning outcomes specified in the Semester Learning Plan (RPS) compared to classes that do not use the activity-based SCL method.